An intelligent preparation process for efficient lithium-based oxygen-generating molecular sieves

Through intelligent preparation technology, using ultrasonic, microwave and magnetic processing technologies, combined with the analysis of crystal guide agents and crystal development index, the constant temperature crystallization time of lithium-based oxygen-making molecular sieve is accurately controlled, which solves the problem of crystal maturity and improves its adsorption performance.

CN118579807BActive Publication Date: 2024-12-24LUOYANG XINLING WEINA NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410717479.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2024-12-24
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

During the preparation of lithium-based oxygen-making molecular sieve, the uncertainty of the constant temperature crystallization time leads to insufficient growth or overgrowth of the crystal, affecting its pore structure and adsorption performance.

Method used

Using intelligent preparation technology, through ultrasonic dispersion, microwave processing, magnetic stirring and spray drying, combined with the preparation of crystal guide agent and the analysis of crystal development index, the constant temperature crystallization time is accurately controlled to ensure the full maturity of the crystal.

Benefits of technology

The adsorption performance of lithium-based oxygen-generating molecular sieve to small molecules such as oxygen is significantly improved, impurities are involved and changes in the pore structure, and the efficiency of the oxygen-generating process is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118579807B_ABST
    Figure CN118579807B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of molecular sieves for environmental governance and restoration, and specifically to an intelligent preparation process for an efficient lithium-based oxygen-producing molecular sieve, the process comprising: mixing bentonite, laponite, pyrophyllite, and lithium magnesium silicate, adding them to a sulfuric acid solution after crushing, dispersing after heating, filtering, washing, and drying; mixing zeolite, palygorskite, and pearlite, cooling after calcination, and crushing; mixing the dried powder with the crushed powder, adding deionized water, stirring magnetically after microwave, and drying to obtain a powder; preparing a crystal directing agent; mixing sodium hydroxide, sodium aluminate, and sodium silicate nonahydrate, adding deionized water, adding the dried powder, heating and stirring to stand, adding a crystal directing agent and heating and stirring, heating again and crystallizing at a constant temperature, immersing the molecular sieve in a lithiated solution, heating and roasting under reduced pressure, and activating to obtain a lithium-based oxygen-producing molecular sieve. The present application controls the crystallization time and improves the preparation quality of the lithium-based oxygen-producing molecular sieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of molecular sieves for environmental governance and restoration, and specifically to an intelligent preparation process for a high-efficiency lithium-based oxygen-producing molecular sieve. Background Art

[0002] Lithium-based oxygen molecular sieve is a synthetic hydrated aluminum silicate material with the function of screening molecules. As an environmental governance and restoration material, lithium-based oxygen molecular sieve plays an important role in the field of environmental restoration. It can replenish oxygen in outdoor activities and ensure the safety of people in plateaus and deep sea environments. At the same time, it can adsorb nitrogen and provide a higher purity oxygen production environment. Due to its unique physical and chemical properties, lithium-based oxygen molecular sieve is mainly used in the adsorption oxygen production process in industry, that is, it selectively adsorbs nitrogen and oxygen in the air through its pore structure, thereby achieving oxygen enrichment or separation.

[0003] In the process of preparing lithium-based oxygen-generating molecular sieves, since there are certain differences in the composition and proportion of the raw materials used in each preparation process, the time required for constant temperature crystallization is also different in the preparation process of different batches, so it is necessary to strictly control the time of constant temperature crystallization. If the crystallization time is too short, the molecular sieve crystals may not grow fully, the crystals are small and incomplete, and the pore structure and pore distribution of the molecular sieve are affected, thereby reducing its adsorption performance; if the crystallization time is too long, impurities may participate in the crystallization process, causing excessive crystal growth and larger crystal size, which in turn causes changes in the pore structure of the lithium-based molecular sieve, affecting its adsorption performance for small molecules such as oxygen. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides an intelligent preparation process for a high-efficiency lithium-based oxygen-producing molecular sieve to solve the existing problems.

[0005] The intelligent preparation process of a high-efficiency lithium-based oxygen-generating molecular sieve in this application adopts the following technical solution:

[0006] An embodiment of the present application provides an intelligent preparation process for a high-efficiency lithium-based oxygen-producing molecular sieve, the method comprising the following steps:

[0007] S1, mixing bentonite, laponite, pyrophyllite and lithium magnesium silicate uniformly, crushing and adding into a sulfuric acid solution with a molar concentration of 2 mol / L, heating in a water bath and then ultrasonically dispersing, filtering, washing and drying;

[0008] S2, mixing stilbite, palygorskite and nacre evenly, calcining and cooling to room temperature, and pulverizing;

[0009] S3, mixing the powders obtained from S1 and S2, adding deionized water to form a suspension, subjecting the suspension to microwave treatment, magnetic stirring, and spray drying to form a powder;

[0010] S4, selecting various raw materials for preparing a crystal directing agent, and performing reaction treatment to obtain the crystal directing agent;

[0011] S5, mixing the sodium hydroxide, sodium aluminate and sodium silicate nonahydrate in the raw material S4 evenly, adding deionized water, stirring evenly, adding the powder obtained in S3, heating and stirring and standing for aging, then adding the crystal directing agent, heating in a water bath for stirring reaction, heating again and crystallizing at a constant temperature in a glass crystallization kettle;

[0012] Determine the crystallization matching index based on the precipitation characteristics during the constant temperature crystallization process, and then construct a crystallization development index; based on the crystallization development index, obtain the crystallization maturity index to control the constant temperature crystallization time;

[0013] After the crystallization is completed, the mixture is filtered and washed with water until it is neutral, and then dried, ground, and sieved to obtain a molecular sieve;

[0014] S6, immersing the molecular sieve in a lithiated solution, placing the molecular sieve for filtration, taking out the molecular sieve, and subjecting the molecular sieve to multiple reduced pressure heating and reduced pressure calcination to activate the molecular sieve to obtain a lithium-based oxygen-producing molecular sieve.

[0015] Preferably, the solid-liquid ratio of the crushed powder to the sulfuric acid solution in S1 is 1:12-16, the mixture is heated in a water bath to 75-95° C., and ultrasonically dispersed for 16-32 minutes.

[0016] Preferably, the calcination temperature in S2 is 750-850° C., and the calcination time is 1-2 hours.

[0017] Preferably, the magnetic stirring time in S3 is 25 to 35 min, and the rotation speed is 1600 to 2000 r / min.

[0018] Preferably, the specific steps of preparing the crystal directing agent in S4 are:

[0019] Select bentonite 10-16, stilbite 4-10, laponite 5-11, sodium metasilicate nonahydrate 20-29, sodium hydroxide 15-24, sodium metaaluminate 11-15;

[0020] The bentonite, stilbite and laponite are mixed uniformly, calcined at 650-680°C for 1-2h, naturally cooled to room temperature, mixed with a sulfuric acid solution with a molar concentration of 1.6 mol / L in a solid-liquid ratio of 1:15-18, heated in a water bath to 72-82°C, kept warm for 20-40min, filtered, washed and dried, calcined at 850-900°C for 2-3h, naturally cooled to room temperature, crushed, ground and sieved to obtain a powder A for use;

[0021] Take the sodium hydroxide solution and pour it into the deionized water equivalent to 12 to 15 times of the sodium hydroxide solution, add the powder A to be used, mix and stir evenly, add sodium metasilicate nonahydrate and sodium metaaluminate, heat at 75 to 85° C. for 1 to 2 hours, cool to room temperature, and then stand and age for 20 to 24 hours to obtain a crystal directing agent.

[0022] Preferably, the heating and stirring in S5 is stirring at 72-81°C for 2.5-4.5 hours, the water bath heating temperature is 93-113°C, the stirring reaction time is 4.5-6.5 hours, and the re-heating temperature is 108-119°C.

[0023] Preferably, the method for determining the crystallization matching index is:

[0024] The crystallization image at each time point is obtained, and a square window is constructed with each pixel in the crystallization image as the center. The grayscale difference between any two pixels in the window is forward fused as the crystallization matching index of the pixel in the center of the window. Accordingly, the crystallization matching index of all pixels in the crystallization image is obtained.

[0025] Preferably, the method for constructing the crystallization development index is:

[0026] The crystallization matching indexes of all pixels in the crystallization image are clustered, and the mean value of the crystallization matching index of each cluster is recorded as the crystallization characteristic value of each cluster;

[0027] The ratio of the crystallization eigenvalue of the cluster where each pixel is located to the sum of the crystallization eigenvalues ​​of all clusters is recorded as the crystallization weight of each pixel;

[0028] The cumulative result of the product of the crystallization weight and the gray value of all pixels in the crystallization image is taken as the crystallization development index of the crystallization image.

[0029] Preferably, the crystal maturity index is obtained to control the constant temperature crystallization time, and the specific process is:

[0030] The crystallization development indexes of the crystallization images at multiple time points before each time point are combined into a crystallization observation sequence at each time point, and a first-order difference is performed to obtain a crystallization generation sequence;

[0031] Taking each crystal growth index in the crystallization generation sequence as an independent variable of the sign function, obtaining the sign term of each crystal growth index, and forming a crystallization trend sequence with the sign terms of all the crystal growth indexes in the crystallization generation sequence;

[0032] The ratio of the sum of the number of symbol items with symbol items of -1 and 0 in the crystallization trend sequence to the total number of symbol items in the crystallization trend sequence is used as the crystallization slowdown weight, and the sum of the normalized results according to the reciprocals of all crystallization development indexes in the crystallization generation sequence is multiplied by the crystallization slowdown weight to obtain the crystallization maturity index at each time point;

[0033] When the normalized crystallization maturity index at multiple consecutive time points is greater than or equal to the crystallization maturity index threshold, the constant temperature crystallization is terminated.

[0034] Preferably, the lithiation solution of S6 uses ethanol as solvent and lithium perchlorate as lithium salt, and the concentration is 1 mol / L. The reduced pressure heating is reduced pressure heating at 81-92°C for 1-2h, the reduced pressure calcination is reduced pressure calcination at 168-188°C for 2-3h, and the activation is activation at 285-325°C for 3-4 hours.

[0035] This application has at least the following beneficial effects:

[0036] The present application constructs a crystallization matching index by analyzing the precipitation characteristics of crystals during the constant temperature crystallization process, reflecting the degree to which each pixel in the crystallization image belongs to the crystallization area; based on the crystallization matching index, the crystallization degree is analyzed and a crystallization development index is constructed, reflecting the crystallization degree in the crystallization image at the current time point; based on the crystallization development index, the changing trend of the crystallization growth rate is analyzed and a crystallization maturity index is constructed, reflecting the degree to which the constant temperature crystallization process should be terminated at the current time point; based on the crystallization maturity index, the duration of constant temperature crystallization is controlled, which solves the problem of impurity crystallization, excessive crystal growth, and changes in pore structure caused by too long crystallization time, and significantly improves the adsorption performance of lithium-based oxygen-generating molecular sieves for small molecules such as oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 A flowchart of the steps of an intelligent preparation process for a high-efficiency lithium-based oxygen-generating molecular sieve provided in this application;

[0039] Figure 2 This is a schematic diagram of crystallization image acquisition;

[0040] Figure 3 This is a schematic diagram of crystal development index analysis;

[0041] Figure 4Schematic diagram of clustering effect;

[0042] Figure 5 This is the flow chart of constant temperature crystallization time control. DETAILED DESCRIPTION

[0043] In order to further explain the technical means and effects adopted by this application to achieve the predetermined invention purpose, the following is a detailed description of the intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve proposed in this application, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "another embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0044] Unless otherwise defined, terms such as "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a circuit structure, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such articles or devices. In the absence of further restrictions, an element defined by the statement "comprising a ..." does not exclude the presence of other identical elements in the article or device comprising the element. In addition, the term "and\or" used herein includes any and all combinations of one or more related listed items. All technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present application belongs.

[0045] The specific scheme of the intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve provided in the present application is described in detail below with reference to the accompanying drawings.

[0046] An embodiment of the present application provides an intelligent preparation process for a highly efficient lithium-based oxygen-generating molecular sieve. For details, please refer to Figure 1 , the method comprises the following steps:

[0047] S1: Bentonite, laponite, pyrophyllite and lithium magnesium silicate are mixed uniformly, crushed and passed through a 200-mesh sieve, and then, as the first embodiment of the present application, the sieved powder is added to a sulfuric acid solution with a molar concentration of 2 mol / L at a solid-liquid ratio of 1:12, heated in a water bath to 75° C., ultrasonically dispersed for 16 minutes, and filtered, washed and dried for standby use;

[0048] Preferably, in the second embodiment of the present application, the solid-liquid ratio of the sieved powder to the sulfuric acid solution is 1:14, the water bath heating temperature is 85° C., and the ultrasonic dispersion time is 24 min;

[0049] Preferably, in the third embodiment of the present application, the solid-liquid ratio of the sieved powder to the sulfuric acid solution is 1:16, the water bath heating temperature is 95° C., and the ultrasonic dispersion time is 32 min.

[0050] S2: Mix stilbite, palygorskite and nacre evenly, preferably, as the first embodiment of the present application, calcine at 750° C. for 1 h, cool naturally to room temperature, and grind, pass through a 200-mesh sieve, and set aside;

[0051] Preferably, as the second embodiment of the present application, in step S2, the calcination temperature is 800° C. and the calcination time is 1.5 h;

[0052] Preferably, as the third embodiment of the present application, in step S2, the calcination temperature is 850°C and the calcination time is 2 hours.

[0053] S3: the powder obtained in step S1 and the powder obtained in step S2 are mixed evenly, and an appropriate amount of deionized water is added to prepare a suspension with a concentration of 60%, and the mixture is subjected to microwave treatment for half an hour at a microwave power of 450 W, followed by magnetic stirring for 25 minutes at a rotation speed of 1600 r / min, and then spray-dried into powder for standby use;

[0054] Preferably, as the second embodiment of the present application, in step S3, the magnetic stirring time is 30 minutes, and the rotation speed is 1800 r / min;

[0055] Preferably, as the third embodiment of the present application, in step S3, the magnetic stirring time is 35 minutes and the rotation speed is 2000 r / min.

[0056] S4: preparing a crystal directing agent, selecting raw materials: bentonite, stilbite, laponite, sodium metasilicate nonahydrate, sodium hydroxide, and sodium metaaluminate;

[0057] Preferably, in the first embodiment of the present application, the weight parts of each raw material are 10 parts of bentonite, 4 parts of stilbite, 5 parts of laponite, 20 parts of sodium metasilicate nonahydrate, 15 parts of sodium hydroxide, and 11 parts of sodium aluminate; then, the bentonite, stilbite, and laponite are evenly mixed and calcined to obtain a calcined solid, the calcination temperature is 650° C., and the calcination time is 1 hour;

[0058] After naturally cooling to room temperature, the calcined solid is mixed with a sulfuric acid solution. In the first embodiment of the present application, the calcined solid is mixed with a sulfuric acid solution with a molar concentration of 1.6 mol / L at a solid-liquid ratio of 1:15, heated to 72°C in a water bath, kept warm for 20 minutes, filtered, washed, and dried, calcined in an environment of 850°C for 2 hours, naturally cooled to room temperature, and crushed and ground, passed through a 200-mesh sieve, and the specific sieving mesh number can be selected by the implementer according to the actual situation, to obtain a stand-by powder A;

[0059] Afterwards, pour the sodium hydroxide solution into deionized water equivalent to 13 times the amount thereof, then add the standby powder A, mix well, add sodium metasilicate nonahydrate and sodium aluminate under stirring, heat at 75°C for 1 hour, cool to room temperature with water, and allow to stand for aging for 20 hours to obtain a crystal directing agent.

[0060] Preferably, as the second embodiment of the present application, in step S4, the weight parts of each raw material are 13 bentonite, 7 zeolite, 8 hectorite, 25 sodium metasilicate nonahydrate, 20 sodium hydroxide, and 13 sodium aluminate; in the second embodiment, the calcination temperature is 665°C and the calcination time is 1.5h; the solid after calcination is mixed with a sulfuric acid solution with a molar concentration of 1.6mol / L at a solid-to-liquid ratio of 1:16, heated to 77°C in a water bath, kept warm for 30min, filtered, washed, and dried, calcined in an environment of 875°C for 2.5h, naturally cooled to room temperature, and crushed and ground, passed through a 200-mesh sieve to obtain a stand-by powder A; take the sodium hydroxide solution and pour it into deionized water equivalent to 13 times its amount, then add the stand-by powder A, mix evenly, add sodium metasilicate nonahydrate and sodium aluminate under stirring, heat at a heating temperature of 80°C for 1.5h, and stand for aging for 22h to obtain a crystal directing agent.

[0061] Preferably, as the third embodiment of the present application, in step S4, the weight parts of each raw material are respectively 16 bentonite, 10 zeolite, 11 hectorite, 29 sodium metasilicate nonahydrate, 24 sodium hydroxide, and 15 sodium aluminate; in the third embodiment, the calcination temperature is 680°C and the calcination time is 2h; the solid after calcination is mixed with a sulfuric acid solution with a molar concentration of 1.6 mol / L in a solid-liquid ratio of 1:18, heated to 82°C in a water bath, kept warm for 40min, filtered, washed, and dried, calcined at 900°C for 3h, naturally cooled to room temperature, and crushed and ground, passed through a 200-mesh sieve to obtain a stand-by powder A; take the sodium hydroxide solution and pour it into deionized water equivalent to 13 times its amount, then add the stand-by powder A, mix well, add sodium metasilicate nonahydrate and sodium aluminate under stirring, heat at 85°C for 2h, and let stand for aging for 24h to obtain a crystal directing agent.

[0062] S5: Evenly mix sodium hydroxide, sodium aluminate and sodium silicate nonahydrate, then add deionized water equivalent to 20 times the amount of the mixture, stir evenly, and then add the powder obtained in step S3, heat, stir and let stand for aging. The implementer can decide the standing aging time according to the actual application scenario. In this embodiment, it is two days. Then add the crystal directing agent obtained in step S4, heat in a water bath for stirring reaction, heat again, and crystallize at a constant temperature in a glass crystallization kettle. After the reaction is completed, filter and wash with water until the pH is neutral, then dry, grind and sieve.

[0063] Preferably, as the first embodiment of the present application, the heating and stirring in step S5 is stirring at 72°C for 2.5 hours, the water bath heating temperature is 93°C, the stirring reaction time is 4.5 hours, and the temperature for heating again is 108°C;

[0064] Preferably, as the second embodiment of the present application, the heating and stirring in step S5 is stirring at 76°C for 3.5 hours, the water bath heating temperature is 103°C, the stirring reaction time is 5.5 hours, and the temperature for heating again is 113°C;

[0065] Preferably, as the third embodiment of the present application, the heating and stirring in step S5 is stirring at 81°C for 4.5 hours, the water bath heating temperature is 113°C, the stirring reaction time is 6.5 hours, and the temperature for heating again is 119°C.

[0066] Considering that the constant temperature crystallization time has a great influence on the crystallization state when the constant temperature crystallization is carried out in the glass crystallization kettle, the crystallization state in the glass crystallization kettle is analyzed to control the constant temperature crystallization time. The constant temperature crystallization time range is 11 to 16 hours. The specific constant temperature crystallization time control process is as follows:

[0067] Step 1: Collect crystallization images during the constant temperature crystallization process.

[0068] An industrial HD camera is placed in front of the glass crystallization reactor. The industrial HD camera continuously and uninterruptedly collects crystallization images during the constant temperature crystallization process at equal time intervals. The collection diagram is as follows Figure 2 The obtained crystallization image is an image in RGB space, and the crystallization image in RGB space is converted into a crystallization image in gray space by grayscale averaging method. The time interval is taken as an empirical value of 20s in this application.

[0069] Specifically, in Figure 2 In the figure, the device numbered 1 represents a camera, the device numbered 2 represents a coolant, and the device numbered 3 represents a crystallization outlet.

[0070] At this point, a crystallization image is obtained after each acquisition.

[0071] Step 2: Analyze the precipitation characteristics of crystals during the constant temperature crystallization process to construct a crystallization matching index, analyze the degree of crystallization based on the crystallization matching index to construct a crystallization development index, and analyze the growth rate of crystals based on the crystallization development index to construct a crystallization maturity index.

[0072] 1) Construct a crystallization matching index based on the precipitation characteristics of crystals.

[0073] During the isothermal crystallization process, at the microscopic level, since the skeleton of the lithium-based molecular sieve is usually composed of tetrahedral silicon oxygen and aluminum oxygen units, these tetrahedrons are connected by shared oxygen atoms to form a three-dimensional structure with uniform pore size. Therefore, at the macroscopic level, the crystals formed during the isothermal crystallization process should have uniform thickness.

[0074] Since the thickness of the crystals formed during the constant temperature crystallization process is uniform, the grayscale values ​​of the pixels belonging to the crystallization area in the crystallization image should be relatively close. Based on the above analysis, this application constructs a crystallization matching index to reflect the degree to which the pixel belongs to the crystallization area. The construction process of the crystallization matching index is as follows:

[0075] A square window with the pth pixel point in the crystallization image as the center and a side length of b is recorded as a crystallization monitoring window, wherein the value of b in the embodiment is 5. Then the crystallization matching index can be calculated as follows:

[0076] The grayscale difference between any two pixels in the crystallization monitoring window is used as the crystallization difference between the two pixels. Preferably, in this embodiment, the grayscale difference is the absolute value of the difference between the grayscale values ​​of the two pixels. In the specific application process, the implementer can set the grayscale difference measurement method by himself.

[0077] It can be understood that the greater the difference in grayscale values ​​between any two pixels in the window, the more likely it is that there are more impurities or other components in the window, so the greater the difference in crystallinity between the pixel and the center pixel of the window is calculated;

[0078] The forward fusion result of the crystallization difference between all two arbitrary pixels in the crystallization observation window is used as the crystallization matching index. Preferably, in this embodiment, the forward fusion is used to characterize that the change trends between the variables are consistent and the same, and can be analyzed by positive correlations such as multiplication relationship, addition relationship, and mean relationship. In this embodiment, the mean is used for forward fusion, that is, the mean of the crystallization difference between all two arbitrary pixels in the crystallization observation window is used as the crystallization matching index. The specific relationship is determined according to the actual application scenario.

[0079] It should be understood that the greater the difference in crystallization between any two pixels in the crystallization monitoring window, the less the area corresponding to the window meets the crystallization precipitation characteristics, and therefore the smaller the calculated crystallization matching index of the central pixel of the window.

[0080] 2) Construct the crystallization development index based on the crystallization matching index.

[0081] Specifically, the schematic diagram of crystal growth index analysis is as follows Figure 3 shown.

[0082] The crystallization matching index of each pixel point obtained through the above steps reflects the degree to which each pixel point belongs to the crystallization area. At the same time, as the crystallization process continues, the crystal gradually becomes thicker. When light passes through the crystal, Mie scattering may occur, that is, the light is scattered and reflected multiple times in the crystal, which increases the chance of interaction between the light and the crystal, thereby increasing the total amount of scattered light. When there is enough scattered light, the cumulative effect of the scattered light will make the crystal appear white. Therefore, the color of the thicker crystal appears relatively white. Based on the above analysis, this application constructs a crystallization development index based on the crystallization matching index to reflect the crystallization situation in the crystallization image at the current time point. The construction process of the crystallization development index is as follows:

[0083] The crystallization matching index of all pixels in the crystallization image is used as the input of the K-means clustering algorithm. In this embodiment, the size of the necessary parameter cluster number is set to 2, and the output is the clustered pixels.

[0084] Specifically, the clustering effect diagram is as follows: Figure 4 shown.

[0085] The mean of the crystallization matching index of all pixels in each cluster is calculated respectively, and recorded as the crystallization characteristic value of each cluster. The K-means clustering algorithm is a well-known technology, and the specific process is not repeated in this application. Then the crystallization development index of the crystallization image can be calculated as follows:

[0086] The ratio of the crystallization eigenvalue of the cluster where each pixel is located to the sum of the crystallization eigenvalues ​​of all clusters is used as the crystallization weight of each pixel, which reflects the degree to which the pixel belongs to the crystallization region. The larger the crystallization eigenvalue of the cluster where the pixel is located, the more likely the pixel belongs to the crystallization region, so the calculated crystallization weight is larger.

[0087] The cumulative result of the product of the crystallization weight and gray value of all pixels in the crystallization image is taken as the crystallization development index of the crystallization image. The greater the degree to which all pixels in the crystallization image belong to the crystallization area and the closer the pixel color is to white, the more likely it is a thicker crystal, that is, the higher the degree of crystallization, the larger the calculated crystallization development index.

[0088] 3) Construct a crystal maturity index based on the crystal development index.

[0089] The crystallization development index of the crystallization image at each time point obtained through the above steps reflects the degree of crystallization at each time point. As the chemical reaction continues to occur during the constant temperature crystallization process and the raw materials are continuously consumed, the growth rate of the crystal will gradually decrease. When the growth rate of the crystal is low, it indicates that the reaction is close to the end and the constant temperature crystallization process should be terminated to avoid the constant temperature crystallization time being too long, which may cause other impurities to participate in the crystallization process, causing the structure of the lithium-based molecular sieve to change, affecting the adsorption performance of small molecules such as oxygen. Based on the above analysis, this application constructs a crystallization maturity index based on the crystallization development index to reflect the degree to which the constant temperature crystallization process should be terminated. The construction process of the crystallization maturity index is as follows:

[0090] The sequence of crystallization development indexes of the crystallization images at a time point before time point t is recorded as a crystallization observation sequence. If the number of time points before time point t is less than a, the regression filling method is used to make up for it, so that the length of the crystallization observation sequence is a, where a is 15 in the embodiment;

[0091] The sequence obtained by performing the first-order difference of the crystallization observation sequence is recorded as the crystallization generation sequence, and each crystallization development index in the crystallization generation sequence is used as the independent variable of the sign function to obtain the sign term of each crystallization development index in the crystallization generation sequence. The sequence composed of the sign terms of the crystallization generation sequence is recorded as the crystallization trend sequence. The regression filling method and the calculation of the sign function are well-known technologies, and the specific process is not repeated in this application. Then the crystallization maturity index can be calculated, and the calculation method is as follows:

[0092] The ratio of the sum of the number of elements with sign terms of -1 and 0 in the crystallization trend sequence to the total number of sign terms in the crystallization trend sequence is taken as the crystallization slowdown weight;

[0093] It can be understood that the greater the proportion of elements with symbol terms of -1 and 0 in the crystallization trend sequence, the more obvious the slowing trend of the crystal formation rate in the isothermal crystallization process is, and therefore the greater the calculated crystallization slowing weight is;

[0094] The product of the normalized sum of the reciprocals of all elements in the crystallization generation sequence and the crystallization slowdown weight is taken as the crystallization maturity index. In particular, when the element is 0, the normalized result is marked as 0.

[0095] It should be understood that the larger the crystallization slowdown weight is, the more obvious the slowdown trend of the crystal formation rate in the isothermal crystallization process is. At the same time, the larger the normalized sum of the inverses of all elements in the crystallization generation sequence is, the faster the crystal formation rate decreases, that is, the closer it is to the end of the reaction, and the more the isothermal crystallization process should be ended at this time. Therefore, the larger the calculated crystallization maturity index is.

[0096] Step 3: Control the constant temperature crystallization time based on the crystal maturity index.

[0097] The crystallization maturity index at each time point obtained by the above steps reflects the degree to which the constant temperature crystallization process should be terminated at each time point, and the crystallization maturity index at each time point is normalized using the Z-score normalization method to obtain a normalized crystallization maturity index. If the normalized crystallization maturity index at the t time point is greater than or equal to the crystallization maturity index threshold, it indicates that the raw material has been consumed more at this time, the crystallization generation rate is low, and the reaction is close to completion, and the constant temperature crystallization process should be terminated. At the same time, in order to avoid misjudgment caused by the special circumstances of individual time points, in this embodiment, the normalized crystallization maturity index at L consecutive time points is greater than or equal to the crystallization maturity index threshold as the judgment condition for terminating the constant temperature crystallization process, that is, when the crystallization maturity index at L consecutive time points is greater than or equal to the crystallization maturity index threshold, it is determined that the constant temperature crystallization process should be terminated at this time. Wherein the crystallization maturity index threshold value in this embodiment is 0.75, and the embodiment value of L is 7.

[0098] Specifically, the constant temperature crystallization time control process diagram is as follows: Figure 5 shown.

[0099] S6: Using ethanol as solvent and LiClO4 (lithium perchlorate) as lithium salt, a 1 mol / L lithiated solution is prepared, and the molecular sieve obtained in step S5 is immersed in a lithiated solution equivalent to 4 times the amount of the molecular sieve. The implementer can also set the ratio of the lithiated solution to the molecular sieve according to the actual situation; leave it for two days, filter, take out the molecular sieve, and perform reduced pressure heating as the first embodiment of the present application, wherein the reduced pressure heating temperature is 81°C, the reduced pressure heating time is 1h, and then reduced pressure roasting is performed, the reduced pressure roasting temperature is 178°C, and the reduced pressure roasting time is 2h, and this is repeated 3 times. The implementer can set the number of repetitions according to the actual situation. After activation, a high-efficiency lithium-based oxygen-producing molecular sieve is obtained, and the activation temperature is 285°C and the activation time is 3 hours;

[0100] Preferably, as the second embodiment of the present application, in step S6, the reduced pressure heating temperature is 86°C, the reduced pressure heating time is 1.5 hours, and then the reduced pressure roasting is performed, the reduced pressure roasting temperature is 168°C, and the reduced pressure roasting time is 3 hours; the activation temperature is 305°C, and the activation time is 3.5 hours;

[0101] Preferably, as the third embodiment of the present application, the reduced pressure heating temperature is 92°C, the reduced pressure heating time is 2 hours, and then reduced pressure roasting is performed, the reduced pressure roasting temperature is 188°C, and the reduced pressure roasting time is 2.5 hours; the activation temperature is 325°C, and the activation time is 4 hours.

[0102] The performance test results of the high-efficiency lithium-based oxygen-generating molecular sieve prepared according to the above steps and embodiments of the present application are shown in Table 1 below:

[0103] According to the HG / T 2783-1996 molecular sieve crushing resistance test method, the high-efficiency lithium-based oxygen-generating molecular sieve products are tested for crushing resistance;

[0104] According to the GB 6287-86 molecular sieve static water adsorption determination method, the static water adsorption rate of the high-efficiency lithium-based oxygen-generating molecular sieve product is tested at 10% humidity and 25°C (1);

[0105] According to the GB 6287-86 molecular sieve static water adsorption determination method, the static water adsorption rate of the high-efficiency lithium-based oxygen-generating molecular sieve product was tested under the conditions of 75% humidity and 35°C (2).

[0106] Table 1

[0107]

[0108]

[0109] It is understood that references to "one embodiment" or "some embodiments" etc. described in the specification of the present application mean that one or more embodiments of the present application include specific features, structures or characteristics described in conjunction with the embodiment. Therefore, if "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appear in different places in this specification, they do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0110] It should be noted that the sequence of the above-mentioned embodiments of the present application is only for description and does not represent the advantages and disadvantages of the embodiments. And the above-mentioned specific embodiments of this specification are described. In addition, the process depicted in the accompanying drawings does not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multi-tasking and parallel processing are also possible or may be advantageous. At the same time, the size of the sequence number of each step in the embodiment does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments in this specification.

[0111] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. An intelligent preparation process for a highly efficient lithium-based oxygen-producing molecular sieve, characterized in that: The process includes the following steps: S1, mixing bentonite, laponite, pyrophyllite and lithium magnesium silicate uniformly, crushing and adding into a sulfuric acid solution with a molar concentration of 2 mol / L, heating in a water bath and then ultrasonically dispersing, filtering, washing and drying; S2, mixing stilbite, palygorskite and nacre evenly, calcining and cooling to room temperature, and pulverizing; S3, mixing the powders obtained from S1 and S2, adding deionized water to form a suspension, subjecting the suspension to microwave treatment, magnetic stirring, and spray drying to form a powder; S4, selecting various raw materials for preparing a crystal directing agent, and performing reaction treatment to obtain the crystal directing agent; S5, mixing the sodium hydroxide, sodium aluminate and sodium silicate nonahydrate in the raw material S4 evenly, adding deionized water, stirring evenly, adding the powder obtained in S3, heating and stirring and standing for aging, then adding the crystal directing agent, heating in a water bath for stirring reaction, heating again and crystallizing at a constant temperature in a glass crystallization kettle; Determine the crystallization matching index based on the precipitation characteristics during the constant temperature crystallization process, and then construct a crystallization development index; based on the crystallization development index, obtain the crystallization maturity index to control the constant temperature crystallization time; After the crystallization is completed, the mixture is filtered and washed with water until it is neutral, and then dried, ground, and sieved to obtain a molecular sieve; S6, immersing the molecular sieve in a lithiation solution, placing it in a filtration chamber, taking out the molecular sieve, and subjecting it to multiple reduced pressure heating and reduced pressure calcination to activate the molecular sieve to obtain a lithium-based oxygen-producing molecular sieve; The method for determining the crystallization matching index is: Acquire the crystallization image at each time point, construct a square window with each pixel in the crystallization image as the center, forward fuse the grayscale difference between any two pixels in the window as the crystallization matching index of the pixel in the center of the window, and accordingly, obtain the crystallization matching index of all pixels in the crystallization image; The method for constructing the crystallization development index is: The crystallization matching indexes of all pixels in the crystallization image are clustered, and the mean value of the crystallization matching index of each cluster is recorded as the crystallization characteristic value of each cluster; The ratio of the crystallization eigenvalue of the cluster where each pixel is located to the sum of the crystallization eigenvalues ​​of all clusters is recorded as the crystallization weight of each pixel; The accumulated result of the product of the crystallization weight and the gray value of all pixels in the crystallization image is taken as the crystallization development index of the crystallization image; The crystal maturity index is obtained to control the constant temperature crystallization time, and the specific process is as follows: The crystallization development indexes of the crystallization images at multiple time points before each time point are combined into a crystallization observation sequence at each time point, and a first-order difference is performed to obtain a crystallization generation sequence; Taking each crystal growth index in the crystallization generation sequence as an independent variable of the sign function, obtaining the sign term of each crystal growth index, and forming a crystallization trend sequence with the sign terms of all the crystal growth indexes in the crystallization generation sequence; The ratio of the sum of the number of symbol items with symbol items of -1 and 0 in the crystallization trend sequence to the total number of symbol items in the crystallization trend sequence is used as the crystallization slowdown weight, and the sum of the normalized results according to the reciprocals of all crystallization development indexes in the crystallization generation sequence is multiplied by the crystallization slowdown weight to obtain the crystallization maturity index at each time point; When the normalized crystallization maturity index at multiple consecutive time points is greater than or equal to the crystallization maturity index threshold, the constant temperature crystallization is terminated.

2. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The solid-liquid ratio of the crushed powder in S1 to the sulfuric acid solution is 1:12-16, heated in a water bath to 75-95° C., and ultrasonically dispersed for 16-32 minutes.

3. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The calcination temperature in S2 is 750-850° C., and the calcination time is 1-2 hours.

4. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The magnetic stirring time in S3 is 25 to 35 minutes, and the rotation speed is 1600 to 2000 r / min.

5. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The specific steps of preparing the crystal directing agent in S4 are: Select bentonite 10-16, stilbite 4-10, laponite 5-11, sodium metasilicate nonahydrate 20-29, sodium hydroxide 15-24, sodium metaaluminate 11-15; The bentonite, stilbite and laponite are mixed uniformly, calcined at 650-680°C for 1-2h, naturally cooled to room temperature, mixed with a sulfuric acid solution with a molar concentration of 1.6 mol / L in a solid-liquid ratio of 1:15-18, heated in a water bath to 72-82°C, kept warm for 20-40min, filtered, washed and dried, calcined at 850-900°C for 2-3h, naturally cooled to room temperature, crushed, ground and sieved to obtain a powder A for use; Take the sodium hydroxide solution and pour it into the deionized water equivalent to 12 to 15 times of the sodium hydroxide solution, add the powder A to be used, mix and stir evenly, add sodium metasilicate nonahydrate and sodium metaaluminate, heat at 75 to 85° C. for 1 to 2 hours, cool to room temperature, and then stand and age for 20 to 24 hours to obtain a crystal directing agent.

6. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The heating and stirring in S5 is stirring at 72-81° C. for 2.5-4.5 hours, the water bath heating temperature is 93-113° C., the stirring reaction time is 4.5-6.5 hours, and the re-heating temperature is 108-119° C.

7. The intelligent preparation process of a high-efficiency lithium-based oxygen-producing molecular sieve according to claim 1, characterized in that: The lithiation solution of S6 uses ethanol as solvent and lithium perchlorate as lithium salt, and the concentration is 1 mol / L. The reduced pressure heating is reduced pressure heating at 81-92°C for 1-2h. The reduced pressure calcination is reduced pressure calcination at 168-188°C for 2-3h. The activation is activation at 285-325°C for 3-4 hours.